(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In this study researcher investigated the differential predictor of teenagers’ academic stress to coping strategies, parental attachment and social support. Social support did not emerge as effective predictor of the certain variables of academic stress.